2017
DOI: 10.3389/fnagi.2017.00393
|View full text |Cite
|
Sign up to set email alerts
|

Biosystems Study of the Molecular Networks Underlying Hippocampal Aging Progression and Anti-aging Treatment in Mice

Abstract: Aging progression is a process that an individual encounters as they become older, and usually results from a series of normal physiological changes over time. The hippocampus, which contributes to the loss of spatial and episodic memory and learning in older people, is closely related to the detrimental effects of aging at the morphological and molecular levels. However, age-related genetic changes in hippocampal molecular mechanisms are not yet well-established. To provide additional insight into the aging p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 70 publications
1
2
0
Order By: Relevance
“…The 860 DEGs were analyzed using the functional annotation tool DAVID Bioinformatics Resources (2021 Update). Age-regulated DEGs and their main functions were in agreement with previous results [ 41 , 42 , 43 ] and external publications [ 44 , 45 ] and identified immune process and transcriptional regulations, inflammation, and cytokine production as regulators in brain aging. Consistent with this, marker genes indicative of activated astrocytes and microglial cells were found to be more highly expressed in the old brain [ 39 , 46 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The 860 DEGs were analyzed using the functional annotation tool DAVID Bioinformatics Resources (2021 Update). Age-regulated DEGs and their main functions were in agreement with previous results [ 41 , 42 , 43 ] and external publications [ 44 , 45 ] and identified immune process and transcriptional regulations, inflammation, and cytokine production as regulators in brain aging. Consistent with this, marker genes indicative of activated astrocytes and microglial cells were found to be more highly expressed in the old brain [ 39 , 46 ].…”
Section: Discussionsupporting
confidence: 91%
“…Li and colleagues identified 1054 DEGs in the hippocampus of 24- vs. 2-month-old male C57BL/6J mice that are closely related to neuroinflammation and involved in the regulation of immune processes, confirming our analysis [ 35 ]. Wang and colleagues analyzed the intersection of 139 up-regulated genes in the hippocampus of 24- and 29-month-old male C57BL/6 mice compared with 3-month-old mice and detected similar processes to our analysis: immune system process, innate immune response, defense response to viruses, and inflammatory response [ 44 ]. A cell type-specific analysis in the hippocampus is certainly worthwhile, as such an analysis in the whole brain has shown that aging triggers specific transcriptional processes in different cell types and that individual genes can be oppositely regulated between different cell types [ 47 ].…”
Section: Discussionmentioning
confidence: 65%
“…14-3-3ζ is a key regulator that mediates signal transduction by binding to phosphoserine-containing proteins during the hippocampal aging process 28. Upregulation of 14-3-3ζ helps to promote hippocampal development 29. Moreover, 14-3-3ζ is potentially a regulator with a similar function to that of β-catenin, which is a central effector of Wnt signaling in metastasis.…”
Section: Discussionmentioning
confidence: 99%